Evaluation of cytokine expression and circulating immune cell subsets as potential parameters of acute radiation toxicity in prostate cancer patients - Stanojković, Tatjana P.; Matić, Ivana Z.; Petrović, Nina; Stanković, Vesna; Kopčalić, Katarina; Besu, Irina; Đorđić Crnogorac, Marija; Mališić, Emina; Mirjačić-Martinović, Katarina; Vuletić, Ana; Bukumirić, Zoran; Žižak, Željko; et al. (Scientific reports, 2020)
One of the challenges of radiation oncology in the era of personalized medicine is identification of biomarkers associated with individual radiosensitivity. The aim of research was to evaluate the possible clinical value of the associations between clinical, physical, and biological factors, and risk for development of acute radiotoxicity in patients with prostate cancer. The study involved forty four patients treated with three-dimensional conformal radiotherapy. The concentrations of IL-1β, IL-2, IL-6, IFN-γ and TGF-β1 were assessed before radiotherapy, after 5th, 15th and 25th radiotherapy fractions, at the end, and 1 month after the end of radiotherapy. Cytokine gene expression was determined in peripheral blood mononuclear cells. The univariate analysis of circulating cytokine levels during radiotherapy showed that increased serum concentrations of IL-6 were significantly associated with higher grade of acute genitourinary toxicity. The multivariate analysis demonstrated that increased level of IL-6 during the radiotherapy was significantly associated with higher grade of acute genitourinary toxicity across treatment. TGF-β expression levels significantly decreased during course of radiotherapy. Research indicates that changes in circulating cytokine levels might be important parameter of radiotoxicity in patients with prostate cancer. These findings suggest that future studies based on multi-parameter examination are necessary for prediction of individual radiosensitivity.